Significantly Decreased Islet β Cell Function is Closely Associated with Hyperglycemia in Chronic Hepatitis B Patients. (30th August 2021) - Liu, Dafeng; Zhou, Lingyun; Zhang, Xinyi; Zeng, Yilan; Bai, Lang; Wu, Dongbo; Tang, Hong
Abstract : Aim . This study is aimed at the characteristics of glucose metabolism and islet β cell function evaluated by the homeostasis model assessment of β cell function (HOMA- β ) value and its risk factors in chronic hepatitis B (CHB) patients. Method . This cross-sectional study recruited 110 CHB patients (CHB group) and 110 patients without hepatitis B virus (non-HBV group); the groups were matched according to sex, age, and body mass index under the same glucose metabolism status. The risk factors, characteristics, and differences in glucose metabolism and HOMA- β values between the two groups were analyzed. Results . The abnormal glucose metabolism rate was higher in CHB patients with liver cirrhosis (LC) or hepatitis B envelope antigen (HBeAg) (−) status. In addition, under the same glucose metabolism status, the fasting plasma glucose (FPG) levels and 2-hour postprandial plasma glucose (2h-PG) levels in the CHB group were higher, while the HOMA- β values were significantly lower and the homeostasis model assessment of insulin resistance (HOMA-IR) value was not higher than that in the non-HBV group (all P < 0.0001 ). Further analyses revealed that the main risk factors for abnormal glucose metabolism were HBeAg (−) status and hepatitis B envelope antibody levels. But HBV serological and virological indicators had no effects on the HOMA- β values. Conclusion . Islet β cell function in patients with CHB was compromised, which is closely associated with fasting and postprandial hyperglycemia in chronic hepatitis B patients. Further research should be done to verify the compromised islet β cell function and then to investigate the mechanisms behind the effect of hepatitis B virus infection on islet β cell function in CHB patients.